2019
DOI: 10.1371/journal.pone.0213938
|View full text |Cite
|
Sign up to set email alerts
|

Physicians and nurses’ knowledge and attitudes towards advance directives for cancer patients in Saudi Arabia

Abstract: This study aimed to investigate physicians’ and nurses’ knowledge and attitudes toward advance directives (ADs) for cancer patients, which empower patients to take decisions on end-of-life needs if they lose their capacity to make medical decisions. A cross-sectional study was conducted using convenience sampling. The outcomes were responses to the knowledge and attitude questions, and the main outcome variables were the total scores for knowledge and attitudes toward ADs. This study included 281 physicians an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
(34 reference statements)
0
15
1
3
Order By: Relevance
“…For example, mental health professionals who comprised physicians, nurses, auxiliary nursing care technicians, psychologists, and social workers had very positive attitudes regarding AD (mean, 80.53; range, 0-90) [26]. In a comparative study [29,30], nurses and physicians showed very high positive attitudes, while nurses' attitudes (mean, 19.5; range, 0-27) were more positive than those of physicians (mean, 15.1; range, 0-27) [29]. Interestingly, compared to EMTs, nurses had more knowledge but less positive attitudes.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…For example, mental health professionals who comprised physicians, nurses, auxiliary nursing care technicians, psychologists, and social workers had very positive attitudes regarding AD (mean, 80.53; range, 0-90) [26]. In a comparative study [29,30], nurses and physicians showed very high positive attitudes, while nurses' attitudes (mean, 19.5; range, 0-27) were more positive than those of physicians (mean, 15.1; range, 0-27) [29]. Interestingly, compared to EMTs, nurses had more knowledge but less positive attitudes.…”
Section: Discussionmentioning
confidence: 97%
“…Different measures of knowledge also prevent comparing our results and previous findings. Further, a wide variety in the level of knowledge about ACP and ADs exists according to the areas of practice or specialty/expertise [26,29,30]. Nonetheless, in a systematic synthesis of three survey studies that examined nurses' AD-related concepts, approximately 60% of knowledge was correct among nurses, with the knowledge of critical care nurses being higher than that of oncology and emergency care nurses [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the number of female nurses in the study was far more than male nurses, the results of this study showed that being a female nurse and working at a medical ward were positive predictors of ACP knowledge of terminally ill patients among nurses. A study in Saudi Arabia showed that women had better knowledge on advanced directives for patients with cancer than their male counterparts [14]. In the previous study considering learning motivation, women had a higher level of autonomy in learning motivation than men, that is, women had better motivation to learn independently, and thus, they could take the initiative to learn to maintain their professional knowledge [15,16].…”
Section: Factors Affecting the Kap-acp Of Terminally Ill Patients Among Nursesmentioning
confidence: 96%